PSYHOSOCIAL FACTORS OF ADAPTATION POTENCIAL - DZÎC Ilona (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The article describes the role of factors promoting or letting adaptation, which are conditionally divided into two large groups: external (social) and internal (personal). External factors included a set of criteria that are most associated with social determinants, as opposed to internal ones, which are associated with individual properties of personality.